The rate commitment to ISO 214 standard among the persian abstracts of approved research projects at school of health management and medical informatics, Isfahan University of Medical Sciences, Isfahan, Iran - Papi, Ahmad; Khalaji, Davoud; Rizi, Hasan Ashrafi; Shabani, Ahmad; Hassanzadeh, Akbar (Journal of Education and Health Promotion, 2014)
Commitment to abstracting standards has a very significant role in information retrieval. The present research aimed to evaluate the rate of Commitment to ISO 214 Standard among the Persian abstracts of approved research projects at School of Health Management and Medical Informatics, Isfahan University of Medical Sciences, Isfahan, Iran. This descriptive study used a researcher-made checklist to collect data, which was then analyzed through content analysis. The studied population consisted of 227 approved research projects in the School of Health Management and Medical Informatics, Isfahan University of Medical Sciences during 2001-2010. The validity of the checklist was measured by face and content validity. Data was collected through direct observations. Statistical analyzes including descriptive (frequency distribution and percent) and inferential statistics (Chi-square test) were performed in SPSS-16. The highest and lowest commitment rates to ISO 214 standard were in using third person pronouns (100%) and using active verbs (34/4%), respectively. In addition, the highest commitment rates to ISO 214 standard (100%) related to mentioning third person pronouns, starting the abstract with a sentence to explain the subject of the research, abstract placement, and including keyword in 2009. On the other hand, during 2001-2003, the lowest commitment rate was observed in reporting research findings (16/7%). Moreover, various educational groups differed significantly only in commitment to study goals, providing research findings, and abstaining from using abbreviations, signs, and acronyms. Furthermore, educational level of the corresponding author was significantly related with extracting the keywords from the text. Other factors of ISO 214 standard did not have significant relations with the educational level of the corresponding author. In general, a desirable rate of commitment to ISO 214 standard was observed among the Persian abstracts of approved research projects at the School of Health Management and Medical Informatics of Isfahan University of Medical Sciences. However, commitment rates differed between years. In addition, commitment to ISO 214 standard was not significantly related with educational group and level.